EKSISTENSI MURAL SEBAGAI AKTIVASI RUANG PUBLIK DI LINGKUNGAN KOTA PADANG - Muhammad Riski; Heldi Heldi (Serupa The Journal of Art Education, 2020)
The presence of murals can be found in several public spaces in Padang City. It's not something new, but the presence of mural still gets pros and cons. Murals in public spaces have different forms, techniques, functions and meanings because they affect the purpose and function of the place. The aim of the author is to examine the presence of murals in public spaces to describe the form (visual), techniques, function of murals, styles (patterns) and the meaning of murals in public spaces in Padang City, with the title "The Existence of Murals as Activation of Public Spaces inPadang City". Data were collected using observation, interview and documentation techniques. The results of the research on the presence of murals in the public space of the city of Padang, the writer can conclude quite well, It's just that it takes development and observation from the artist when making a mural in a public space, because the presence of a mural in a public space is not just a desire, but it can also provide a new perspective for the general public who see and enjoy mural work in publicspaces.Kata kunci : Mural, Aktivasi, Ruang Publik, Bentuk, Teknik, Fungsi, Corak danMakna Mural, Kota Padang